High-efficiency removal of antibiotics through self-assembly formation of layered double hydroxides in wastewater. (April 2023) - Xie, Yuan; Kong, Fanping; Mi, Zhiwei; Huang, Hanhan; Xia, Caifeng; Ma, Zequn; Li, Shuang; Zhang, Qian; Meng, Zilin
Abstract: In this study, to achieve high-efficiency utilization of charges on layered double hydroxides (LDHs), a simple and direct synthesis method of LDHs in wastewater was designed for the removal of the contaminants ciprofloxacin (CIP) and tetracycline (TC). The obtained LDHs structure was characterized by XRD, FT-IR, DLS, SEM and TEM. The removal of CIP/TC using different Mg/Al ratios and stepwise experiments was investigated. With the formation of LDHs structures in wastewater, the CIP/TC molecule was sandwiched between the LDHs layers and removal process was controlled by the positive charges, resulting in a more efficient utilization of the LDHs layer than that of other methods. The removal of CIP was dominant during competitive removal. The isothermal model of the Generalized Langmuir model obtained a good fit with the experimental data in the single and mixed systems, indicating a specific number of adsorption sites on the LDHs layer, and heterogeneous adsorption sites with different adsorption energies. According to the site energy distribution theory, the calculated average energies of CIP and TC were 18.68 and 16.68 J·mmol −1, respectively, under competitive adsorption. Molecular simulation was conducted to explain the interaction between the CIP/TC molecule and LDHs layer based on the electron density and bonding energy. Moreover, the effects of pH, ion coexistence, and antibiotic competition were investigated, which revealed favorable adsorption stability parameters. Therefore, this method for LDHs formation in wastewater allowed the efficient utilization of positive charges and provided a promising method for antibiotic removal. Graphical abstract: Unlabelled Image Highlights: LDHs were directly formed in wastewater to remove antibiotics simultaneously. Higher adsorption capacity is obtained with the efficient use of positive charges. CIP occupied higher-energy sites by site energy distribution theory and GL model. Molecular simulation explained the interactions of antibiotics and LDHs layer.